The Use of Short Stories and Phonemic Awareness in the EFL Classroom to Improve Students’ Reading and Writing Skills - Sánchez Vílchez, Sara (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2023)
This study aims to analyse the impact of using children’s literature in the English foreign language (EFL) classroom on students’ motivation and reading habits, as well as the role of phonics and phonemic awareness in improving reading skills and confidence. the objectives include identifying students’ reading habits and motivation in english and Spanish, identify ing difficulties in reading English and the impact on motivation, analysing perception of time spent in reading activities, and studying the correlation between phonemic awareness and phonics in building better readers. The study will also examine the amount of new words acquired through the process and draw conclusions about the role of motivation in reading and language learning. The results show that the use of short stories in the classroom, combined with phonemic instruction, can be considered as a valuable tool in the english language classroom for students of all ages, as they helped students to increase spelling and vocabulary acquisition. Both factors in combination have helped to increase motivation among students towards language learning. apart from that, this combination of factors creates a synergy in which there is a continuous feedback loop between them